1985
DOI: 10.1073/pnas.82.11.3940
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y injected in the paraventricular hypothalamus: a powerful stimulant of feeding behavior.

Abstract: Neuropeptide Y (NPY) was injected directly Into the paraventricular nucleus of the hypothalamus (PVN) of satiated, brain-cannulated rats, and food and water intake were measured 0.5, 1, 2, 4, and 22 hr postinjection. NPY (24, 78, 235, 783, and 2351 pmol/0.3 pl) produced a large, dosedependent increase in food intake as well as a small increase in water intake. The latency to eat was about 10 min, with substantial feeding occurring in the first 30 min. At doses below 78 pmol, the eating generally occurred only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
273
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 625 publications
(282 citation statements)
references
References 27 publications
8
273
0
1
Order By: Relevance
“…When NPY is injected intracerebroventricularly (i.c.v. ) or directly into the hypothalamus, feeding is markedly increased (Haynes et al, 1998;Stanley & Leibowitz, 1985). This stimulatory e ect has been reported not only in rodents (Iyengar et al, 1999;Levine & Morley, 1984;Morley et al, 1987a, b), but also in virtually all vertebrates that have been studied (Boswell et al, 1993;Kuenzel et al, 1987;Kulkoskyfeeding.…”
Section: Introductionmentioning
confidence: 80%
“…When NPY is injected intracerebroventricularly (i.c.v. ) or directly into the hypothalamus, feeding is markedly increased (Haynes et al, 1998;Stanley & Leibowitz, 1985). This stimulatory e ect has been reported not only in rodents (Iyengar et al, 1999;Levine & Morley, 1984;Morley et al, 1987a, b), but also in virtually all vertebrates that have been studied (Boswell et al, 1993;Kuenzel et al, 1987;Kulkoskyfeeding.…”
Section: Introductionmentioning
confidence: 80%
“…Further studies are required to determine whether NH pups show lower metabolic rate than MS pups per se after repeated weight cycles. NPY potently stimulates food intake, [15][16][17] food deprivation increases the hypothalamic mRNA expression and release of NPY, 31,[36][37][38] and increased expression of the hypothalamic NPY appears to be implicated in the induction of hyperphagia. 39,40 These reports support the idea that increased expression of NPY in the arcuate nucleus of NH/RF pups responding to the first fasting trial on PND 29 might have contributed, at least partly, to the compensatory hyperphagia on PND 30.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 NPY, a potent orexic peptide, stimulates feeding. [15][16][17] Several results suggest that glucocorticoids regulate the hypothalamic NPY expression: adrenalectomy downregulates the expression of NPY gene in the hypothalamus; 18 NPY neurons in the hypothalamic arcuate nucleus contain glucocorticoid receptors 19 and elevated plasma corticosterone appears to be necessary for fastinginduced increase in NPY mRNA expression. 20,21 These reports led us to hypothesize that neonatal MS may lead to development of eating disorders in the offspring later in life, possibly, due to altered HPA axis characteristics modulating the hypothalamic expression of feeding peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal maternal separation, an animal model of stressful experiences in childhood, can permanently modify the characteristics of HPA axis in the offspring (Plotsky and Meaney, 1993;Suchecki and Tufik, 1997;van Oers et al, 1998;Liu et al, 2000). Neuropeptide Y (NPY), the most potent orexic peptide known, stimulates feeding (Stanley and Leibowitz, 1985;Kalra et al, 1999;Schwartz et al, 2000). Previous studies have reported that experiences of maternal separation during pre-weaning period (MS) increase the hypothalamic NPY level in rats later in life (Jimenez-Vasquez et al, 2001;Husum and Mathe, 2002), and that the hypothalamic NPY expression is dis-regulated in MS rats in relation with the HPA axis dysfunction Ryu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%